Pernikahan Dini Meningkatkan Risiko Kejadian Kanker Serviks - Kurniasari Pratiwi; Yuni Fitriana (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2021)
Background: The incidence and mortality from cervical cancer (cervical cancer) in theworld second only to breast cancer. Meanwhile, in developing countries still ranks asthe top cause of cancer deaths in the reproductive age. Cancer of the cervix is still athreat for women so it is called the